Determination of Political Accountability of Village Government: A Study of Village Fund Management in Binuang District - Umi Umairah Suhardi; Fitriani Sari Handayani Razak; Nurhaerani Tenriwaru; Ridwan; Ahmad Amiruddin (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2025)
Accountability is a principle that ensures that government administration is accountable for a series of designed programs. This study aims to examine the influence of success factors in village government accountability in managing village funds, namely, village apparatus competence, community participation, utilization of information technology, organizational commitment, and internal government control systems. The type of research used is quantitative, using component-based or variant-based Structural Equation Modeling (SEM) techniques with Partial Least Square (PLS) as a tool for conducting validity tests. Sampling using the method purposive sampling, thus obtaining 87 respondents with the criteria of village governments directly involved in administering village funds in Binuang District, Polewali Mandar Regency. The results of this study indicate that not all variables can influence accountability in village fund management in Binuang District. For example, village apparatus competence, community participation, information technology utilization, and internal government control systems have a positive effect on accountability in village fund management. However, organizational commitment does not affect accountability in village fund management. Therefore, accountability in village fund management has not been fully able to realize the achievement of good governance in Binuang District, Polewali Mandar Regency